Are we meeting the informational needs of cancer patients and families? Perception of physician communication in pediatric oncology. Issue 9 (2nd January 2019) - Levine, Deena R.; Liederbach, Erik; Johnson, Liza‐Marie; Kaye, Erica C.; Spraker‐Perlman, Holly; Mandrell, Belinda; Pritchard, Michele; Sykes, April; Lu, Zhaohua; Wendler, Dave; Baker, Justin N.
Abstract : Background: High‐quality oncology care is marked by skillful communication, yet little is known about patient and family communication perceptions or content preferences. Our study sought to elicit pediatric oncology patient and parent perceptions of early cancer communication to establish whether informational needs were met and identify opportunities for enhanced communication throughout cancer care. Method: An original survey instrument was developed, pretested, and administered to 129 patients, age 10‐18 years, and their parents at 3 cancer centers between 2011 and 2015. Statistical analysis of survey items about perceived communication, related associations, and patient/parent concordance was performed. Results: A greater percentage of participants reported "a lot" of discussion about the physical impact of cancer (patients, 58.1% [n = 75]; parents, 69.8% [n = 90]) compared with impact on quality of life (QOL) (patients, 44.2% [n = 57]; parents, 55.8% [n = 72]) or emotional impact (patients, 31.8% [n = 41]; parents, 43.4% [n = 56]). One fifth of patients (20.9% [n = 27]) reported they had no up‐front discussion about the emotional impact of cancer treatment. Parents indicated a desire for increased discussion regarding impact on family life (27.9% [n = 36]), long‐term QOL (27.9% [n = 36]), and daily activities (20.2% [n = 26]). Patients more frequently than parents indicated a desire for increased physician/patient discussion around the impact on daily activities (patients, 40.3% [n = 52]; parents, 21.7% [n = 28]; P  < .001), long‐term QOL (patients, 34.9% [n = 45]; parents, 16.3% [n = 21]; P  < .001), pain management (patients, 23.3% [n = 30]; parents, 7% [n = 9]; P  < .001), physical symptom management (patients, 24% [n = 31]; parents, 7.8% [n = 10]; P  < .001), short‐term QOL (patients, 23.3% [n = 30]; parents, 9.3% [n = 12]; P  = .001), and curative potential (patients, 21.7% [n = 28]; parents, 8.5% [n = 11]; P  = .002, P values calculated using McNemar's test). Conclusion: Oncologists may not be meeting the informational needs of many patients and some parents/caregivers. Communication could be enhanced through increased direct physician–patient communication, as well as proactive discussion of emotional symptoms and impact of cancer on QOL. Abstract : This multi‐institutional survey study of pediatric oncology patients and parents describes the perceptions of physician–parent and physician–patient communication in oncology to establish whether informational needs are met. The results highlight key differences in perceived patient and parent communication experiences, content, and preferences and identifies opportunities for enhanced communication early in cancer care.